Impacts on gut microbiota of rats with high-fat diet supplemented by herbs of Melissa officinalis, Lavandula angustifolia and Salvia officinalis - Bilan, Maryna; Bilan, M. V.; Bilan, M.; Білан, Марина Володимирівна; Lieshchova, M. O.; Lieshchova, M. А.; Lieshchova, M.; Lieshchova, Maryna; Lieshchova, Marina; Лєщова, Марина Олексіївна; Brygadyrenko, V. V.; Brygadyrenko, Victor; et al. (Oles Honchar Dnipropetrovsk National University, 2023)
Medicinal plants are used in traditional, folk medicine and veterinary practice to treat and prevent exacerbations of chronic diseases, diseases of the cardiovascular and nervous systems, respiratory and digestive organs, liver, bile ducts, kidneys, urinary tract, to regulate metabolism and to boost immunity, etc. The therapeutic effect on the body is exerted by biologically active substances (alkaloids, glycosides, tannins, essential oils, and others) that are present in various parts of plants. Understanding the issue of interaction between the intestinal microbiota and drugs based on medicinal plants will contribute to the development of treatment protocols for various diseases, including chronic ones, by the normalization of impaired functions due to plant origin substances. In this study, we determined the effect of Melissa officinalis, Lavandula angustifolia, Salvia officinalis on the intestinal microbiota of white rats fed a high-fat diet. The addition of 5% crushed young dry shoots of S. officinalis, L. angustifolia, M. officinalis to the high-fat diet of laboratory rats significantly changed the quantitative ratio of Escherichia coli with normal and altered enzymatic properties in the intestinal content. The number of typical E. coli in rats fed with S. officinalis and L. angustifolia decreased by 1.7 and 1.6 times; non-lactose fermenting form of E. coli, on the contrary, increased by 1.8–2.1 times in rats fed with any of the medicinal plants compared to the control. Amid the addition of medicinal plants to the diet, it was not possible to isolate opportunistic enterobacteria of the genus Citrobacter, however, an increase in the number of the genus Candida fungi was observed. Лікарські рослини використовують у традиційній, народній медицині та ветеринарії для лікування та профілактики загострень хронічних захворювань, захворювань серцево-судинної та нервової систем, органів дихання та травлення, печінки, жовчних шляхів, нирок, сечовивідних шляхів, для регуляції обміну речовин, підвищення імунітет і ін. Лікувальну дію на організм надають біологічно активні речовини (алкалоїди, глікозиди, дубильні речовини, ефірні олії та ін.), що містяться в різних частинах рослин. Розуміння питання взаємодії кишкової мікробіоти з препаратами на основі лікарських рослин сприятиме розробці протоколів лікування різноманітних захворювань, у тому числі хронічних, шляхом нормалізації порушень функцій за рахунок речовин рослинного походження. У цьому дослідженні ми визначили вплив Melissa officinalis, Lavandula angustifolia, Salvia officinalis на мікробіоту кишечника білих щурів, яких годували дієтою з високим вмістом жиру. Додавання 5 % подрібнених молодих сухих пагонів S. officinalis, L. angustifolia, M. officinalis до високожирного раціону лабораторних щурів істотно змінювало кількісне співвідношення Escherichia coli з нормальними та зміненими ферментативними властивостями у кишковому вмісті. У щурів, яким згодовували S. officinalis і L. angustifolia, кількість типових E. coli зменшувалася в 1,7 і 1,6 раза; неферментуючої лактозу форми E. coli, навпаки, у щурів, які отримували будь-яку з лікарських рослин, збільшувалася в 1,8–2,1 рази порівняно з контролем. При додаванні до раціону лікарських рослин не вдалося виділити умовно-патогенні ентеробактерії роду Citrobacter, однак спостерігалося збільшення чисельності грибів роду Candida.
Вплив лікарських рослин Melissa officinalis, Lavandula angustifolia та Salvia officinalis на мікробіоту кишечника щурів за раціону з високим вмістом жиру
Білан Марина Володимирівна https://orcid.org/0000-0003-3178-201X Лєщова Марина Олексіївна http://orcid.org/0000-0002-4251-4152
Keywords: male white rats; самці білих щурів; medicinal plants; лікарські рослини; Lamiaceae; губоцвіті; high-fat diet; дієта з високим вмістом жирів; gut microbiota; кишкова мікробіота; dysbiosis; дисбіоз